Mother–Son Communication About Sex and Routine Human Immunodeficiency Virus Testing Among Younger Men of Color Who Have Sex With Men - Bouris, Alida; Hill, Brandon J.; Fisher, Kimberly; Erickson, Greg; Schneider, John A. (Journal of adolescent health, 2015)
The purposes of this study were to document the HIV testing behaviors and serostatus of younger men of color who have sex with men (YMSM) and to explore sociodemographic, behavioral, and maternal correlates of HIV testing in the past 6 months. A total of 135 YMSM aged 16–19 years completed a close-ended survey on HIV testing and risk behaviors, mother–son communication, and sociodemographic characteristics. Youth were offered point-of-care HIV testing, with results provided at survey end. Multivariate logistic regression analyzed the sociodemographic, behavioral, and maternal factors associated with routine HIV testing. A total of 90.3% of YMSM had previously tested for HIV, and 70.9% had tested in the past 6 months. In total, 11.7% of youth reported being HIV positive, and 3.3% reported unknown serostatus. When offered an HIV test, 97.8% accepted. Of these, 14.7% had a positive oral test result, and 31.58% of HIV-positive YMSM (n = 6) were seropositive unaware. Logistic regression results indicated that maternal communication about sex with males was positively associated with routine testing (odds ratio = 2.36; 95% confidence interval = 1.13–4.94). Conversely, communication about puberty and general human sexuality was negatively associated (odds ratio = .45; 95% confidence interval = .24–.86). Condomless anal intercourse and positive sexually transmitted infection history were negatively associated with routine testing; however, frequency of alcohol use was positively associated. Despite high rates of testing, we found high rates of HIV infection, with 31.58% of HIV-positive YMSM being seropositive unaware. Mother–son communication about sex needs to address same-sex behavior as this appears to be more important than other topics. YMSM with known risk factors for HIV are not testing at the recommended time intervals.